INTEGRAL MARKETING TECHNOLOGICAL PLAN APPLIED TO THE DEVELOPMENT OF VETERINARIES, IN THE CITY OF RIOBAMBA - Aguilar Cajas, Héctor Oswaldo; Rivera Abarca, Ana Lucía; Miranda Salazar, Maria Fernanda (mktDESCUBRE, 2020)
The migration of companies to digital platforms has become imperative, the development of a technological plan was carried out with the purpose of proposing an alternative that efficiently increases the sales of products and services related to the upbringing and quality of life of the pets of the city of Riobamba. Nowadays, the acquisition of pets as family members, as companions of affection, friends of walking, sports or care, has become common and a basis for this is the desire to link veterinarians with pet owners. The creation of the plan, makes it easier for pet owners to find a stable place for their medical care, the purchase of pet supplies, and the benefits that locals can offer. In the absence of a record of the number of pets, the calculation for the surveys was made from the PEA of the city of Riobamba, where a number of 382 people was obtained and for the veterinary and related surveys a total of 45. The proposal of this application aims to help veterinary owners with the influx of frequent customers. Given this, a saving was obtained in the feasibility analysis.